A systematic review and meta‐analysis on the effectiveness of web‐based psychosocial interventions among patients with colorectal cancer. (20th April 2022) - Wan, Su Wei; Chng, Yun Jia Devon; Lim, Siew Hoon; Chong, Choon Seng; Pikkarainen, Minna; He, Hong‐Gu
Abstract: Aims: To synthesize the effectiveness of web‐based psychosocial interventions on self‐efficacy, anxiety, depression, quality of life (QoL), non‐specific psychological and cancer‐specific distress among patients with colorectal cancer (CRC). Design: A systematic review and meta‐analysis. Data sources: Six databases (PubMed, PsycINFO, Embase, Scopus, CINAHL and CNKI) were searched from inception to December 2021. Review methods: Experimental/quasi‐experimental studies involving patients with CRC for the improvement of aforementioned outcomes were included. Two reviewers screened and extracted the data, and assessed studies' methodological quality using risk of bias tools. Meta‐analyses and narrative syntheses were performed. Results: Nineteen studies consisting of 1386 participants were identified. Cognitive‐behavioural therapy delivered online was the most common trialled web‐based psychosocial intervention. Meta‐analyses revealed no positive effect for self‐efficacy (standardized mean difference 0.93, 95% CI: 0.52 to 1.35, p < .01) and minimal benefit for QoL (mean difference [MD] 2.83, 95% CI: −0.31 to 5.98, p = .08) but significant positive effects for anxiety (MD −2.23, 95% CI: −3.31 to −1.14, p < .01) and depression (MD −2.84, 95% CI: −4.09 to −1.59, p < .01) among CRC survivors in the intervention group as compared with the control group. Narrative synthesis suggested possible benefits in reducing distress. Conclusion: Web‐based psychosocial interventions are promising alternatives to conventional delivery methods in reducing patients' anxiety, depression and distress. However, evidence on self‐efficacy and QoL remains inconsistent. More adequately powered, well‐designed trials with targeted and theory‐based interventions are required to ascertain findings. Impact: By highlighting the potential of web‐based psychosocial interventions in reducing anxiety and depression among CRC survivors, this review has put forth beneficial information supporting the use and acceptance of web‐based care delivery in light of COVID‐19 restrictions and nationwide lockdowns. Meanwhile, the paucity of empirical support reflects the necessity of more extensive research to test and improve other health outcomes. PROSPERO registration number: CRD42021261396